Treatment of radius, ulna and humerus fractures with the aid of a bone morphogenetic protein in a giant anteater (Myrmecophaga tridactyla) - Ferrigno, C. R. A.; Futema, F.; Fedullo, D. L.; Kyan, V.; Fantoni, D. Tabacchi; Baccarin, D. C. B.; Romano, M. A. (Veterinary and Comparative Orthopaedics and Traumatology, 2003)
A giant anteater (Myrmecophaga tridactyla) was found with closed comminuted fractures on the right radius and ulna and left humerus the duration of which was unknown. The animal was unable to use either of the thoracic limbs. The fractures were stabilized with 3.5-mm titanium plates and a commercially available mixture of micro lyophilized bovine cortical osseous and bovine BMP (Gen-tech®, Baumer, Brazil) was implanted into the fractures sites. Postoperative radiographic evaluations were performed every 30 days and after four months. Bone healing was observed in all of the fractures. The animal was able to be reintroduced into its natural habitat. From this case we conclude that despite the low metabolic rate of the giant anteater, which is an inherent characteristic of this species, the treatment of radius, ulna and humerus fractures by means of plates and screws, associated with BMP on the Myrmecophaga tridactyla, was a success.
Keywords: Anteater; BMP; fracture